2018
DOI: 10.1093/ajcn/nqy165
|View full text |Cite
|
Sign up to set email alerts
|

Plasma fatty acids in de novo lipogenesis pathway are associated with diabetogenic indicators among adults: NHANES 2003–2004

Abstract: Background Insulin regulates fatty acids (FAs) in the blood; conversely, FAs may mediate insulin sensitivity and are potentially modifiable risk factors of the diabetogenic state. Objective The objective of our study was to examine the associations between plasma concentrations of FAs, fasting plasma glucose (FPG), and glycated hemoglobin (HbA1c) among individuals (n = 1433) in the NHANES (2003–2004). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
3
5
0
Order By: Relevance
“…MUFAs (C16:1 and 18:1) are major components of triglycerides, cholesterol esters and phospholipids, produced by de novo lipogenesis and carried in VLDL in the circulation [15]. This incorporation of MUFAs in VLDL, could partly explain the observed association between high levels of MUFAs and the MU phenotype, characterized by high levels of triglycerides, total cholesterol and LDL-C. Our findings are also supported by results from a NHANES survey where higher plasma concentration of SFAs and MUFAs were associated with increased levels of fasting plasma glucose and HbA1c [32]. The same pattern was found in the FINRISK study.…”
Section: Discussionsupporting
confidence: 85%
“…MUFAs (C16:1 and 18:1) are major components of triglycerides, cholesterol esters and phospholipids, produced by de novo lipogenesis and carried in VLDL in the circulation [15]. This incorporation of MUFAs in VLDL, could partly explain the observed association between high levels of MUFAs and the MU phenotype, characterized by high levels of triglycerides, total cholesterol and LDL-C. Our findings are also supported by results from a NHANES survey where higher plasma concentration of SFAs and MUFAs were associated with increased levels of fasting plasma glucose and HbA1c [32]. The same pattern was found in the FINRISK study.…”
Section: Discussionsupporting
confidence: 85%
“…They concluded that low PUFA and high MUFA levels are biomarkers for future cardiovascular risk [18]. In the NHANES-study, they found that high plasma concentrations of SFA and MUFA were associated with elevated HbA1c and fasting plasma glucose levels [43]. In our study there was a positive correlation between HbA1c and 22:5n3.…”
Section: Discussionsupporting
confidence: 67%
“…Firstly, the three saturated and two mono-unsaturated NEFAs are all considered to be primary products of de novo lipogenesis. 58 There are indications that plasma NEFAs resulting from this process are most strongly associated with diabetes incidence. 29 Secondly, all five have either been shown to, or can be predicted to, bind to the NEFA binding site FA2 with high affinity.…”
Section: Resultsmentioning
confidence: 99%